Challenging case of disseminated tuberculosis in an immunocompetent adult - Narjes Abid; Ella Nemsi; Siwar Sbaihi; Rahma Ayadi; Manel Loukil; Nada Gader; Khaoula Hemissi; Hedia Ghrairi (Future Science OA, 2024)
Disseminated tuberculosis (TB) is a TB infection involving two or more noncontiguous sites. It is a challenging medical care due to its misleading presentation. Although it is associated with immunodepression, rare cases have been described in immunocompetent patients.We report the case of a 27-year-old immunocompetent man who presented with an altered general condition and dyspnea. Chest computed tomography (CT) revealed pulmonary masses and mediastinal lymphadenopathy. Sputum smear microscopy for acid-fast bacilli was negative. Scannoguided transparietal lung biopsy was performed twice with inflammatory tissue in histological study. A surgical lung biopsy was then made. The histopathology report confirmed TB involving lung, pleura and lymph nodes. A few days after antituberculosis therapy was started, the patient developed psychomotor slowing related to quadriportal hydrocephalus. He benefited from ventriculoperitoneal bypass. Polymerase chain reaction for detection of Mycobacterium TB was positive in cerebrospinal fluid.In conclusion: The diagnosis of disseminated TB is challenging owing to its non-specific clinical and radiological presentation and the frequent negativity of biological fluids for tubercle bacilli. Molecular biology should always be considered in front of lingering symptoms, particularly in endemic areas, given their speed and sensitivity, thus avoiding invasive diagnostic procedures, as was the case with our patient.